Contacts between Greece and Pannonia in the Early Iron Age with Special Concern to the Area of Thessalonica - Potrebica, Hrvoje (2008)
It seems that in the Late Bronze Age some general cultural and religious concepts were common throughout Europe, from Scandinavia to Greece. The general pattern of social and economic structure, probably partly determined by the climate, was similar over a large area that included both Greece and Central Europe. After that period the cultural development in those two areas followed different patterns, resulting in two fundamentally different cultural complexes of the Early Iron Age. Although the communication between these two areas fundamentally changed, it never ceased. In the Early Iron Age, Greece became one of the most powerful cultural centres on the Mediterranean. A significant increase in quantity and quality of production of art objects and objects of common use was related to the intensive development of trade activity. Some of that activity was directed northwards and it had reflections even in Pannonia and the area of the Hallstatt Culture. The area between Pannonia and Greece is geographically very complex, not easily passable, and split into a large number of smaller defined areas. The best solution to this problem would be the establishment of a relay trade system and a complex communication network. The goods that travelled across such great distances, both spatially and culturally, must have had great potential when they were able to characterize, if not even induce such contacts. There are some finds from northern and Central Balkans in Greece, although the finds of distinctively Pannonian origin are scarce. This group of finds, mainly consisting of pieces of horse equipment, pendants and several types of fibulae and pins, cannot justify the effort and risk of communication with those areas, and we must presume that goods that were transported southward were perishable (perhaps precious metals, amber or other rare raw materials). A special class of objects that are defined as prestigious goods, like bronze vessels and defensive weapons, could trigger and/or influence the course of material and spiritual development of the local society. In order to find out how these processes work, it is necessary to study the notion and mechanisms of import which can roughly be divided into three main categories including the import of objects, the import of ideas and concepts, and the import of technology and craftsmanship. The distribution of prestigious goods in the area between Pannonia and Greece, as well as study of mechanisms of their transition and function within different cultural contexts, offers some insight into all three aspects of import. However, objects were not the only thing that travelled along those ancient routes. If we perceive culture as cargo, the objects of prestige present strong conceptual vessels capable of carrying sets of ideas over long distances and open more or less stable communication channels for further transfer.
Projekt MZOS
Projekt MZOS
ENG